Genewise detection of variants in MEFV gene using nanopore sequencing - Ghukasyan, Lilit; Khachatryan, Gisane; Sirunyan, Tamara; Minasyan, Arpine; Hakobyan, Siras; Chavushyan, Andranik; Hayrapetyan, Varduhi; Ghazaryan, Hovsep; Martirosyan, Gevorg; Mkrtchyan, Gohar; Vardanyan, Valentina; Mukuchyan, Vahan; et al. (Frontiers in Genetics, 2024)
Familial Mediterranean Fever (FMF) is a genetic disorder with complex inheritance patterns and genotype-phenotype associations, and it is highly prevalent in Armenia. FMF typically follows an autosomal recessive inheritance pattern (OMIM: 249100), though it can occasionally display a rare dominant inheritance pattern with variable penetrance (OMIM։134610). The disease is caused by mutations in the MEFV gene, which encodes the pyrin protein. While the 26 most prevalent mutations account for nearly 99% of all FMF cases, more than 60 pathogenic mutations have been identified. In this study, we aimed to develop an affordable nanopore sequencing method for full-length MEFV gene mutation detection to aid in the diagnosis and screening of FMF. We employed a multiplex amplicon sequencing approach, allowing for the processing of up to 12 samples on both Flow cells and Flongle flow cells. The results demonstrated near-complete concordance between nanopore variant calling and qPCR genotypes. Moreover, nanopore sequencing identified additional variants, which were confirmed by whole exome sequencing. Additionally, intronic and UTR variants were detected. Our findings demonstrate the feasibility of full-gene nanopore sequencing for detecting FMF-associated pathogenic variants. The method is cost-effective, with costs comparable to those of the qPCR test, making it particularly suitable for settings with limited laboratory infrastructure. Further clinical validation using larger sample cohorts will be necessary.